(untitled) (Journal of Fiber Bioengineering and Informatics, 2019)
We investigated the effect of washing and drying conditions on dimensional change in various articles of knitted clothing, taking into account drying temperature, temperature change during drying, external force at dehydration, external force during drying, and humidity during drying. We immersed samples in water at 25 ± 2◦C for 30 min, then dried them in a chamber at 40, 60, and 80 ◦C, and at 5% relative humidity (RH). We also investigated the effects of increasing the temperature from 40 to 60 ◦C and decreasing it from 60 to 40 ◦C. After dehydration, we dried the samples using a roller and a frontloader washing and drying machine at various humidity levels. We measured dimensional changes in the samples before and after drying. We investigated five samples of knitted clothing: men’s socks, women’s socks, men’s underwear, women’s underwear, and women’s t-shirts. We detected no difference in the dimensional change ratio in the cotton or polyurethane underwear and t-shirts when the drying temperature was varied. However, the dimensional change ratio of acrylic-containing men’s socks varied depending on the drying temperature. When drying acrylic-containing men’s socks from 40 to 60 ◦C, the dimensional change ratio was larger than under other drying conditions. A lower temperature in the final drying stage could effectively reduce the shrinkage of socks made from acrylic, polyester, and polyurethane. The deformation due to external force during dehydration affected dimensional change. The external force during drying also greatly affected dimensional change in the knitted clothing. The humidity and drying time did not affect dimensional change in the knitted cotton clothing.